2002
DOI: 10.1091/mbc.01-10-0500
|View full text |Cite
|
Sign up to set email alerts
|

Cell Cycle-dependent Assembly of a Gin4-Septin Complex

Abstract: Gin4, a Nim1-related kinase, is required in budding yeast for localization of the septins and for proper control of daughter cell growth during G2/M. Gin4 becomes hyperphosphorylated when cells enter mitosis, leading to activation of Gin4 kinase activity. In this study, we have used immunoaffinity chromatography to identify proteins that associate with Gin4 during mitosis, with the goal of finding targets of Gin4 kinase activity and proteins that play a role in Gin4 activation. We show that during mitosis Gin4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
197
3
8

Year Published

2004
2004
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 143 publications
(213 citation statements)
references
References 36 publications
5
197
3
8
Order By: Relevance
“…In this regard, the apparent molecular weight of recombinant complexes isolated at a moderate salt concentration (0.25 M) is consistent with two copies of each septin in a 1:1:1:1 stoichiometry [10], whereas the amount of Cdc11 in native complexes that are isolated at higher salt concentrations (0.5-1.0 M) is substoichiometric [8,38]. Likewise, in high-salt conditions, the amount of Shs1 recovered in native complexes is substoichiometric [39]. Together, these data indicate a model for the complex that is illustrated in Figure 1b.…”
Section: Assembly Of Hetero-oligomeric Multi-septin Complexes In Buddmentioning
confidence: 53%
See 1 more Smart Citation
“…In this regard, the apparent molecular weight of recombinant complexes isolated at a moderate salt concentration (0.25 M) is consistent with two copies of each septin in a 1:1:1:1 stoichiometry [10], whereas the amount of Cdc11 in native complexes that are isolated at higher salt concentrations (0.5-1.0 M) is substoichiometric [8,38]. Likewise, in high-salt conditions, the amount of Shs1 recovered in native complexes is substoichiometric [39]. Together, these data indicate a model for the complex that is illustrated in Figure 1b.…”
Section: Assembly Of Hetero-oligomeric Multi-septin Complexes In Buddmentioning
confidence: 53%
“…Phosphorylation by two protein kinases, Cla4 [28,[66][67][68] and Gin4 [39,48,69], plays a prominent role in initiating and/or stabilizing filament assembly during collar formation during emergence of the bud. Cla4 is a clear-cut ortholog of mammalian p21-activated protein kinases (PAKs), and the closest mammalian relative of Gin4 is the neuron-specific, AMPK-related, kinase-family member, BRSK1.…”
Section: Phosphorylation Exerts Temporal Control On Septin-collar Assmentioning
confidence: 99%
“…To fully understand the phenotypic differences between shs1D cdc10D strain and shs1D cdc11D strain, it is essential to perform analysis of subunit composition of the septin complex produced in these double mutants. Moreover, Mortensen et al (2002) reported that Shs1 interacts with Gin4 kinase independently of Cdc11 in cla4D and nap1D cells. Cdc3 is phosphorylated in vivo, which plays a role in septin ring Figure 7.-Phenotypes of the shs1-100c allele.…”
Section: Shs1 Acts Differently In Cytokinesis From Other Septinsmentioning
confidence: 99%
“…Furthermore, this is associated with coordinated regulation of septin interactions [58] and with a role for Cdc42 [59]. A compelling model has the septin ring in the yeast bud neck acting as a scaffold [20] for the regulated association and dissociation of kinases such as Cla4/PAK, Nim 1/Gin4, and Cdc5/Polo [60][61][62][63][64][65][66][67]. These can then spatially and temporally regulate the activation status of Swe1 and link morphogenetic events to M-phase entry.…”
Section: Septins In Yeastmentioning
confidence: 99%